Relevance of sentinel lymph node biopsy for thick melanoma in the era of immunotherapy. (December 2020) - Picado, Omar; Ryon, Emily L.; Möller, Mecker G.; Goel, Neha; Kesmodel, Susan B.
Abstract: Background: Sentinel lymph node biopsy provides prognostic information in patients with thick melanoma but is often underutilized. We examine regional lymph node evaluation (RLNE) in patients with thick melanoma and the effect on treatment and overall survival (OS). Methods: Patients with clinical T4N0M0 melanoma were selected from the National Cancer Database (2004–2015). Binary logistic regression analysis was used to identify factors associated with RLNE and treatment. Overall survival analysis was performed. Results: A total of 14 286 patients with clinical T4N0M0 melanoma were identified; RLNE was performed in 70.2% of patients, and positive LNs were identified in 27.1%. RLNE was more likely in males (OR:1.44, 95%CI: 1.32–1.56, p < .001), and patients treated at academic centers (OR:1.58, 95%CI:1.46–1.71, p < .001). Immunotherapy was more commonly used in patients with RLNE (13.9% vs 3.4%, p < .001) and was associated with positive LNs (OR:2.50, 95%CI:2.19–2.86, p < .001). The 5-year OS for RLNE was 56.9% and for no RLNE was 32.7%. Independent factors associated with better OS were treatment at an academic center (HR:0.88, 95%CI:0.84–0.93, p < .001), and immunotherapy use (HR:0.86, 95%CI:0.76–0.96, p < .001). Conclusion: The use of RLNE in patients with thick melanoma is important for prognosis and to risk stratify patients for selection of adjuvant therapies and clinical trials. Highlights: Sentinel lymph node biopsy is important for staging, prognosis, and regional disease control in patients with melanoma. Sentinel lymph node biopsy allows for risk stratification of patients with thick melanoma. Use of adjuvant immunotherapy in patients with thick melanoma significantly improves overall survival. Appropriate staging in patients with thick melanoma is important for selection for adjuvant therapy.